Urinary Allantoin Is Elevated in Severe Intraventricular Hemorrhage in the Preterm Newborn - Esiaba, Ijeoma; Angeles, Danilyn M.; Holden, Megan S.; Tan, John B. C.; Asmerom, Yayesh; Gollin, Gerald; Boskovic, Danilo S. (Translational stroke research, 2016)
Germinal matrix intraventricular hemorrhage (IVH) is the most common type of intracranial hemorrhage observed in preterm neonates. It is a precursor of poor neurocognitive development, cerebral palsy, and death. The pathophysiology is not well defined, but damage to the fragile germinal matrix vasculature may be due to free radicals generated during inflammation and as a consequence of ischemia followed by reperfusion. Assessment of the oxidative stress status in these infants is therefore important. Urinary allantoin concentration was measured in preterm neonates as a marker of oxidative stress associated with IVH. Urine was collected from 44 preterm neonates at four time points between 24 and 72 hours of life (HOL), and the allantoin content was determined by gas chromatography mass spectrometry (GCMS). Records were retrospectively reviewed, and the incidence and severity of IVH was categorized as follows: no IVH ( n = 24), mild (grade 1–2) IVH ( n = 13), and severe (grade 3–4) IVH ( n = 7). Neonates with severe IVH showed significantly elevated allantoin levels vs subjects with no IVH from 36 HOL (0.098 ± 0.013 μmol and 0.043 ± 0.007 μmol, respectively, p = 0.002). The allantoin concentration remained elevated even at 72 HOL (0.079 ± 0.014 μmol and 0.033 ± 0.008 μmol, respectively, p = 0.021). There were no significant differences in allantoin levels in the no IVH and mild IVH groups. IVH was diagnosed by head imaging on average at about 11th postnatal day. Urinary allantoin levels were significantly elevated during the first 3 days of life in the neonates subsequently diagnosed with severe IVH, suggesting that oxidative stress might be a crucial factor in IVH pathogenesis. Further studies are needed to assess the usefulness of urinary allantoin in early identification of preterm infants at risk for or with severe IVH and monitoring of the response to interventions designed to prevent or treat it.